Foreign exchange rationing, wheat markets and food security in Ethiopia - Dorosh, Paul A.; Ahmed, Hashim A. (International Food Policy Research Institute, 2009)
In spite of remarkable growth in Ethiopia’s agricultural production and overall real incomes (GDP/capita) from 2004/05 to 2008/09, prices of major cereals (teff, maize, wheat and sorghum) have fluctuated sharply in both nominal and real terms. International prices of cereals also fluctuated widely, particularly between 2006 and 2008. However, the links between Ethiopia’s domestic cereal markets and the international market are by no means straightforward. Among the major staples, only wheat is imported or exported on a significant scale. And frequent changes in trade and macro-economic policies, movements in international prices and fluctuations in domestic production have at times eliminated incentives for private sector imports of wheat. From July 2005 to March 2007, private sector wheat imports were profitable and domestic wheat prices closely tracked import parity prices. Then, from April 2007 to May 2008, good domestic harvests coincided with increase international wheat prices, so private sector wheat imports were no longer profitable. Most recently, rationing of foreign exchange for imports effectively stopped private sector wheat imports beginning in about April 2008. Partial equilibrium analysis shows, however, that government imports and sales in 2008-09 effectively increased domestic supply and lowered market wheat prices. These sales at the low official price also implied that recipient households, traders and flour mills enjoyed a significant subsidy. Allowing the private sector access to foreign exchange for wheat imports or auctioning government wheat imports in domestic markets would eliminate these rents and generate additional government revenue, while having the same effect on market prices as government subsidized sales.